Intellectual property protection in plan varieties: A new worldwide index (1961-2011) - Mercedes Campi; Alessandro Nuvolari (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2013)
In this paper, we construct a new index that measures the strength of intellectual property (IP) protection for plant varieties for 69 countries over the period 1961-2011. We examine the statistical properties of the index and we compare it with other measures of IP protection. We conclude that the indicator provides a reasonable proxy for assessing the relative strength of IP protection in plants across countries. Finally, we study the main determinants of the evolution of the index over time and we find that variables such as GDP per capita, types of political and institutional environment, levels of urbanization and schooling affect the level of IP protection for plant varieties. The TRIPS Agreement appears as an exogenous factor driving the process towards stronger levels of IP protection for all countries.
Keywords: O10; O34; O50; Q19; 330; Intellectual Property Rights; Plant Breeders' Rights; UPOV Convention; International Comparison